Third Chromosome Balancer Inversions Disrupt Protein-Coding Genes and Influence Distal Recombination Events in Drosophila melanogaster. Issue 7 (1st July 2016) - Miller, Danny E; Cook, Kevin R; Arvanitakis, Alexandra V; Hawley, R Scott
Abstract: Balancer chromosomes are multiply inverted chromosomes that suppress meiotic crossing over and prevent the recovery of crossover products. Balancers are commonly used in Drosophila melanogaster to maintain deleterious alleles and in stock construction. They exist for all three major chromosomes, yet the molecular location of the breakpoints and the exact nature of many of the mutations carried by the second and third chromosome balancers has not been available. Here, we precisely locate eight of 10 of the breakpoints on the third chromosome balancer TM3, six of eight on TM6, and nine of 11 breakpoints on TM6B . We find that one of the inversion breakpoints on TM3 bisects the highly conserved tumor suppressor gene p53 —a finding that may have important consequences for a wide range of studies in Drosophila . We also identify evidence of single and double crossovers between several TM3 and TM6B balancers and their normal-sequence homologs that have created genetic diversity among these chromosomes. Overall, this work demonstrates the practical importance of precisely identifying the position of inversion breakpoints of balancer chromosomes and characterizing the mutant alleles carried by them.